A new species of Tamdaora Gorochov, 1998 (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Cui, Zhenzhen; Bian, Xun (Zootaxa, 2025)
Tamdaora spina sp. nov. is described and illustrated. Meanwhile, to help distinguish the new species, we provided the morphological illustrations of Tamdaora magnifica Gorochov, 1998 for comparison. All the specimens were deposited in Guangxi Normal University. This discovery increases the number of Tamdaora species in China from three to four.